2001
DOI: 10.1038/sj.onc.1204685
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer in vivo gene expression profiling assisted by laser capture microdissection and microarray analysis

Abstract: Large scale gene expression pro®ling was carried out on laser capture microdissected (LCM) tumor and normal oral epithelial cells and analysed on high-density oligonucleotide microarrays. About 600 genes were found to be oral cancer associated. These oral cancer associated genes include oncogenes, tumor suppressors, transcription factors, xenobiotic enzymes, metastatic proteins, di erentiation markers, and genes that have not been implicated in oral cancer. The database created provides a veri®able global pro®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
0
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(155 citation statements)
references
References 40 publications
7
146
0
2
Order By: Relevance
“…We generated the signature gene set using a widely accepted statistical method, SAM, that selects genes that are differentially expressed between two groups and estimates a false discovery rate (Tusher et al, 2001). Due to the wide variation in published gene signatures even pertaining to the relatively narrow question of transformation in HNSCC, we considered the accurate prediction of an independent validation set essential to evaluating our results (Alevizos et al, 2001;Mendez et al, 2002;Gonzalez et al, 2003;Hwang et al, 2003;Leethanakul et al, 2003;Ntzani and Ioannidis, 2003). Principal-components analysis is also a useful visual tool but is not considered a robust predictor, and in our hands showed a trend differentiating NÀ from N þ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated the signature gene set using a widely accepted statistical method, SAM, that selects genes that are differentially expressed between two groups and estimates a false discovery rate (Tusher et al, 2001). Due to the wide variation in published gene signatures even pertaining to the relatively narrow question of transformation in HNSCC, we considered the accurate prediction of an independent validation set essential to evaluating our results (Alevizos et al, 2001;Mendez et al, 2002;Gonzalez et al, 2003;Hwang et al, 2003;Leethanakul et al, 2003;Ntzani and Ioannidis, 2003). Principal-components analysis is also a useful visual tool but is not considered a robust predictor, and in our hands showed a trend differentiating NÀ from N þ .…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC may be a useful system for studying lymphatic metastasis because of the high probability of lymphatic spread and low probability of hematogenous spread. A recent study has identified a gene signature for recurrent disease in HNSCC and several studies have investigated the changes in gene expression from normal tissue to carcinoma, but studies involving lymphatic metastasis have been limited by the small number of genes assessed and/or lack of a rigorous efficacy test of the metastatic signature (Alevizos et al, 2001;Belbin et al, 2002;Mendez et al, 2002;Hwang et al, 2003;Gonzalez et al, 2003;Leethanakul et al, 2003;Nagata et al, 2003;Chung et al, 2004;Ginos et al, 2004;Schmalbach et al, 2004;Warner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4 -8 More recent work 9,10 has shown the feasibility of gene expression profiling studies using pure populations of cells obtained with laser capture microdissection (LCM). 11 We modified established protocols [12][13][14] for analyzing mRNA from microdissected frozen tissues and applied this protocol to ethanol-paraffin tissue. The direct comparison of frozen and ethanol-paraffin tissues provides insight into the advantages and disadvantages of each tissue preservation method.…”
Section: (J Mol Diagn 2004 6:371-377)mentioning
confidence: 99%
“…Although no connection between NMU expression and tumor cachexia (Tisdale, 2005) has yet been documented, such a link would be clinically important, as the design of small molecule inhibitors of NMU receptors is feasible. With regard to tumorigenesis, NMU has been shown to be downregulated in oral tumors (Alevizos et al, 2001), identified as an ovarian cancer-associated antigen (Euer et al, 2005), and acts as a potential autocrine growth factor for human myeloid leukemias (Shetzline et al, 2004).…”
Section: Introductionmentioning
confidence: 99%